Contributing Factors That Affect Perception on Malaysia Property Crowdfunding Initiative - Khairul Adlee, Nurul Faziera; Misiran, Masnita (Atlantis Press SARL, 2021)
Crowdfunding has risen as a progressive financing model that enables small businesses to raise funds. In Malaysia, an equity crowdfunding platform has extended innovatively into the proposed property crowdfunding initiative tabled in the Budget 2019. This study was conducted to determine the factors that influence Malaysian perception toward property crowdfunding among young adults. The data were collected using a questionnaire. The questionnaires consisted of 30 questions and were distributed to 60 young adult. SAS Enterprise Guide and Statistical Package for Social Sciences (SPSS) were used to analyze the data. As a result, four factors that influence Malaysian perception toward property crowdfunding among young adult were highlighted: risk tolerance, return expectations, saving expectations, and financial knowledge